Development of a bioanalytical method for quantification of a 15-mer oligonucleotide at sub-ng/ml concentrations using LC–MS/MS. (June 2012) - Hemsley, Martyn; Ewles, Matthew; Goodwin, Lee
LC–MS/MS provides a powerful technique for the selective quantification of therapeutic oligonucleotides; however, the LOQ (typically >1 ng/ml) may be higher than desirable for clinical bioanalysis. A method has been developed to allow quantification of a 15-mer unmodified DNA oligonucleotide in human plasma using SPE and UHPLC with MS/MS detection. The LOQ of this assay was 0.05 nM (∼250 pg/ml). This method was then further developed by the inclusion of online SPE to increase loading and apply additional sample cleanup. This allowed for improved assay precision at lower concentrations and increased signal, thus allowing the method to be validated over the range of 10–4000 pM (approximately 50–20000 pg/ml). The method is accurate, precise and selective and it provides proof-of-concept for sub-ng/ml, high-throughput quantification of oligonucleotides using online SPE coupled to ion-pair, reversed-phase LC–MS/MS.